2020
DOI: 10.1177/2158244020922909
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Leadership, Green Innovation Practices, Environmental Knowledge Learning, and Firm Performance

Abstract: Environmental leadership has received continuous attention from the business sector in recent years, yet few studies have examined the internal mechanisms and contingent conditions that link environmental leadership to firm performance. The aim of this article is to advance research by investigating the relationship between environmental leadership and firm performance by considering the mediating role of green innovation practices and the moderating role of environmental knowledge learning. A questionnaire su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0
23

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(107 citation statements)
references
References 56 publications
5
79
0
23
Order By: Relevance
“…Ethical leaders also set ethical standards in their work and reward ethical behaviors. More and more recent studies have found that ethical leaders have positive impacts on followers' attitudes and behaviors (Jia et al, 2020;Su et al, 2018Su et al, , 2020Wei et al, 2019;Yan et al, 2020). When followers perceive the sense of organizational identity and have achieved returns, they are willing to repay their organizations through active efforts, such as sharing knowledge, thereby contributing to the organizational innovations and productivity (Jia et al, 2020).…”
Section: Ethical Leadership and Employees' Knowledge Sharingmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethical leaders also set ethical standards in their work and reward ethical behaviors. More and more recent studies have found that ethical leaders have positive impacts on followers' attitudes and behaviors (Jia et al, 2020;Su et al, 2018Su et al, , 2020Wei et al, 2019;Yan et al, 2020). When followers perceive the sense of organizational identity and have achieved returns, they are willing to repay their organizations through active efforts, such as sharing knowledge, thereby contributing to the organizational innovations and productivity (Jia et al, 2020).…”
Section: Ethical Leadership and Employees' Knowledge Sharingmentioning
confidence: 99%
“…Known as observational learning (or modeling), this type of learning consists of four steps: attention, retention, reproduction, and motivation. In organizations, leaders possess higher status, formal authority, and control of resources, and they are more likely to be role models for followers (Brown et al, 2005; Su et al, 2020). Social learning theory proposes that people will learn various behaviors by paying attention to, observing and imitating role model behaviors, and establish their own cognitive framework (such as psychological structure) to guide them to imitate these behaviors.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Instead, observing exemplary behavior by EL acts as informative function of reinforcement which sends a signal to employees for imitating EL's behavior. Based on this, employees avidly pay attention to sustainability strategy in order to save or preserve the environment, or at least aspects of it (Su et al, 2020). In line with the premise of social learning theory, empirical evidence has revealed that leaders play an important role in shaping the workplace environment and influencing employees' VEB (al Halbusi et al, 2020; Kuenzi et al, 2020; Lülfs & Hahn, 2013; Walumbwa & Lawler, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A key component of the success achieved to date has been through staff engagement and behavioural changes. In addition to environmental protection and financial savings, these strategies promote environmental awareness, innovation, and greater staff engagement [76,77].…”
Section: Discussionmentioning
confidence: 99%